Assessment of pre-service science teachers’ preference of face-to-face and online learning modes in teacher training institutions - Nwoke, Bright Ihechukwu; Nwaneri, Onyekpandu Meshack; Mohammed, Juliana Isa (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
The study assessed pre-service science teachers' preference for face-to-face and online learning modes in teacher training institutions. Two research questions and two hypotheses were used to direct the study based on the objectives. The study used the descriptive survey research design. From a population of 715 undergraduate final year pre-service science teachers at the school of sciences, Alvan Ikoku Federal College of Education in Owerri, Imo State, Nigeria, 400 pre-service science teachers were selected as a sample. A 4-point Likert-style questionnaire titled "Pre-service Science Teachers Preference of Face-to-Face and Online Learning Modes (PSTPFOLM)" was created by the researcher as the tool for data collection. The instrument had a reliability coefficient of 0.86 determined using Cronbach's alpha formula. The data generated were analyzed using mean and standard deviation to answer research questions while the hypotheses were tested at 0.05 level of significance using a t-test statistical tool. The result of the study revealed that pre-service science teachers preferred face-to-face learning mode to online learning mode. The pre-service science teachers' preference for face-to-face learning mode was not dependent on gender. Based on the findings, it was recommended that online learning mode should be introduced in pre-service science teachers' education through blended learning.